Effect of the Electric Field on the Agyrotropic Electron Distributions. Issue 5 (4th March 2021) - Gao, C.‐H.; Tang, B.‐B.; Li, W. Y.; Wang, C.; Khotyaintsev, Yu V.; Graham, D. B.; Gershman, D. J.; Rager, A. C.; Giles, B. L.; Lindqvist, P. ‐A; Ergun, R. E.; Russell, C. T.; et al.
Abstract: We investigate agyrotropic electron distributions from two magnetopause events observed by magnetospheric multiscale (MMS) spacecraft. Agyrotropic electron distributions can be generated by the finite electron gyration at an electron‐scale boundary, and the electric field normal to this boundary usually contributes to the electron acceleration to make the agyrotropic distributions more apparent. The effect of the electric field becomes important only when it is sufficiently strong and local, meaning its electrostatic potential is comparable to or larger than the electron temperature, and its width is smaller than the electron thermal gyroradius, so that this electric field can directly accelerate part of the electrons out of the original core to form agyrotropic electron distributions. Also, we reproduce the measured electron "finger" structures from test particle simulations, which can be effectively suppressed by increasing the sampling rate of the electron measurement. Plain Language Summary: Agyrotropic electron distributions reveal valuable information of electron dynamics at electron scales, and the generation of these distributions have been extensively studied. In this study, we provide a new possibility to generate agyrotropic electron distributions with a strong localized electric field, which can accelerate part of electrons out of the original electron core to form agyrotropic distributions. As such large‐amplitude small‐scale electric field fluctuations are frequently observed in turbulent plasma environments, we suggest that more agyrotropic electron distributions can be observed with high temporal resolution measurements. Key Points: Agyrotropic electron distributions formed by the finite electron gyration at electron‐scale boundaries and by direct acceleration of a strong local electric field are presented These different processes to generate agyrotropic electron distributions are confirmed by test particle simulations The agyrotropic "finger" distribution measured by magnetospheric multiscale mission/fast plasma investigation can be effectively suppressed by increasing the sampling rate